Towards a Learner-Centered Paradigm: Reconstructing Arabic Language Curriculum for Multidisciplinary University Students - Dr K M A Ahamed Zubair (Yayasan Mutiara Hati Moeslem, 2026)
This study aims to reconstruct the Arabic language curriculum by integrating a learner-centered design paradigm. The reconstruction focuses on two core principles: aligning curricular objectives with specific departmental graduate profiles and accommodating the diverse characteristics of multidisciplinary learners. Conducted at the Department of Arabic, The New College, Chennai, India, the research employed a qualitative descriptive methodology. Data were gathered from 30 undergraduate non-Arabic major students-divided into two cohorts-through semi-structured interviews, classroom observations, and document analysis. The findings propose a four-step reconstruction framework: (1) reformulating instructional objectives to prioritize context-relevant language skills (e.g., reading comprehension for Islamic Studies, speaking skills for Communication); (2) redesigning teaching materials around thematic, field-specific texts and vocabulary; (3) adopting differentiated instructional strategies, including diagnostic pre-testing, heterogeneous grouping, and multimodal methods; and (4) redesigning assessments to be skill-based and aligned with the new objectives. The study concludes that this reconstructed, learner-centric curriculum is essential for enhancing the relevance, effectiveness, and overall quality of Arabic language education in multidisciplinary university settings.